Influence of Education, Religiosity and Believe in Zakat Literature And Distribution of Zakat to BAZNAS Jepara District - Silviana Pebruary; Minas Sirotul Fauziah (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
The potential of zakat can be a solution for improving the Indonesian economy. This study aims to determine education, religiosity, and trust in zakat literacy and to determine zakat literacy on zakat distribution. This study uses descriptive quantitative methods, with multivariate analysis test equipment. The data was obtained through a questionnaire from the people of Jepara who had distributed zakat in BAZNAS, Jepara Regency. The variables studied include; education, religion, belief, literacy of zakat, and distribution of zakat. The results of this study indicate that education and trust have a positive and significant effect on zakat literacy. Religiosity has a positive and insignificant effect on zakat literacy. Zakat literacy has a positive and significant effect on the distribution of zakat